Consumer behavior towards diet and light products (Research, Society and Development, 2023)
This research aimed to evaluate consumer behavior in relation to diet and light products. It was carried out through market research using a structured questionnaire in the city of Barbacena-MG in the first half of 2019, consisting of 385 individuals. Followed by an assessment of acceptance with a 9-point hedonic scale with yogurt in the traditional, light and zero versions, there were two blind situations with information about the versions. Finally, implementation of focus group sessions. Among the test participants, the majority were female, with the minority being those who claim to consume diet and light products, pointing to diet as the main reason for consumption. The most consumed foods include yogurt, followed by soda. Regarding the influence of information on product evaluation, it was observed that information about the yogurt version (light, zero or traditional) did not affect product acceptance. The results suggest that consumers' level of knowledge about diet and light foods is low and they often confuse these two products.